2012
DOI: 10.1152/japplphysiol.01489.2011
|View full text |Cite
|
Sign up to set email alerts
|

Brachial artery adaptation to lower limb exercise training: role of shear stress

Abstract: Lower limb exercise increases upper limb conduit artery blood flow and shear stress, and leg exercise training can enhance upper limb vascular function. We therefore examined the contribution of shear stress to changes in vascular function in the nonexercising upper limbs in response to lower limb cycling exercise training. Initially, five male subjects underwent bilateral brachial artery duplex ultrasound to measure blood flow and shear responses to 30-min cycling exercise at 80% of maximal heart rate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
132
4

Year Published

2013
2013
2019
2019

Publication Types

Select...
3
3
1

Relationship

2
5

Authors

Journals

citations
Cited by 136 publications
(145 citation statements)
references
References 52 publications
9
132
4
Order By: Relevance
“…In agreement with studies of healthy young volunteers (Birk et al 2012;Tinken et al 2008;Tinken et al 2010), two weeks of exercise training in type 2 diabetes and age-matched controls significantly enhanced endothelial function. Whilst continuing exercise training in young healthy controls was associated with return to baseline levels after 6-8 weeks (Birk et al 2012;Tinken et al 2008;Tinken et al 2010), the present study revealed sustained elevation in FMD/GTN-ratios with prolonged training. This suggests that, somewhat in contrast with younger healthy subjects, exercise training leads to improvement in endothelial function that remains elevated in subjects with a priori endothelial dysfunction.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…In agreement with studies of healthy young volunteers (Birk et al 2012;Tinken et al 2008;Tinken et al 2010), two weeks of exercise training in type 2 diabetes and age-matched controls significantly enhanced endothelial function. Whilst continuing exercise training in young healthy controls was associated with return to baseline levels after 6-8 weeks (Birk et al 2012;Tinken et al 2008;Tinken et al 2010), the present study revealed sustained elevation in FMD/GTN-ratios with prolonged training. This suggests that, somewhat in contrast with younger healthy subjects, exercise training leads to improvement in endothelial function that remains elevated in subjects with a priori endothelial dysfunction.…”
Section: Discussionsupporting
confidence: 88%
“…Although we did not directly compare our results to a young control group, the pre-training values of brachial artery FMD in type 2 diabetes and controls (3.4-3.9%) are lower than typically reported in studies examining healthy young men (Tinken et al 2008;Tinken et al 2010;Birk et al 2012). Regarding the impact of exercise training on endothelial function in type 2 diabetes and controls, we did not find a significant change in brachial artery FMD across the 8-week exercise training.…”
Section: Discussioncontrasting
confidence: 85%
See 2 more Smart Citations
“…Several studies have explored the impact of repeated exposure to elevations in antegrade shear stress via training, heating, or in vitro manipulation of antegrade shear 7, 13, 14, 15, 16, 17. These studies consistently report a dose‐dependent increase in arterial caliber and improvement in endothelial function, possibly through upregulation of endothelial nitric oxide synthase 1, 18.…”
Section: Introductionmentioning
confidence: 99%